Strengthening training methods for motor perception ability in tennis - Sun, X. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: Specialized perception in tennis is simply learning the "feel of the ball". Expertise refers to whether a player can handle and control the ball as he wishes, also known as fitness. Objective: Study the effect and mechanism of motion tracking training to improve the perception training methods of tennis players. Methods: This paper conducts a temporal experiment on 38 professional tennis players divided into two groups. The experimental group used optokinetic tracking training for tracking and feedback on their movements. The control group received no interventional treatment. Players` perception and brainwave data at different training times were recorded and analyzed. Results: The subjects in the experimental group had high accuracy in discriminating the spatial location of the ball. The experiment produced a significant occipital M1 signal after the 360ms trial. The M2 signal in the occipital region also had noticeable main effects in each period. The level of the M2 signal in the experimental group showed an increase. Conclusion: Visual motion tracking training has been shown to significantly impact tennis players` perception. This training can improve tennis players` perceptual ability, proving to be an ally in strengthening current training methods.